The help [compact disc, unabridged] - Stockett, Kathryn (Penguin Audio, 2009)
In a time when the civil rights movement is in full force, three women, Minny, Aibileen, and Skeeter, start a movement that puts them all at risk. They show the town that, whether black or white, women can unite.